2019
DOI: 10.1080/08985626.2019.1640459
|View full text |Cite
|
Sign up to set email alerts
|

International networking and knowledge acquisition of Chinese SMEs: the role of global mind-set and international entrepreneurial orientation

Abstract: Chinese small and medium-sized enterprises (SMEs) are increasing their international networking and knowledge acquisition activities. This paper attempts to explain this phenomenon by examining the joint influence of leader global mind-set and firms' international entrepreneurial orientation on those two internationalisation activities. A conceptual model was developed and tested with data from a sample of 208 SMEs in China. The results indicate that both leader global mind-set and firm's international entrepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 103 publications
(138 reference statements)
0
27
0
1
Order By: Relevance
“…The internationalisation process of firms is found to be relatively quickly and their likelihood to be successful is higher when small businesses take advantage of the global networks chain (Felício et al, 2016;Lin et al, 2020). Furthermore, focusing on international SMEs, the literature highlights the entrepreneur's networking capabilities as an indispensable driver of their survival, success, and growth (Garousi Mokhtarzadeh et al, 2021;Karami & Tang, 2019;Lin et al, 2020). In this regard, Andersson and Wictor (2003) found that international entrepreneurs leverage their international experience of living, studying, or working in foreign countries to build formal and informal networks for the international expansion of their ventures.…”
Section: International Networkingmentioning
confidence: 99%
“…The internationalisation process of firms is found to be relatively quickly and their likelihood to be successful is higher when small businesses take advantage of the global networks chain (Felício et al, 2016;Lin et al, 2020). Furthermore, focusing on international SMEs, the literature highlights the entrepreneur's networking capabilities as an indispensable driver of their survival, success, and growth (Garousi Mokhtarzadeh et al, 2021;Karami & Tang, 2019;Lin et al, 2020). In this regard, Andersson and Wictor (2003) found that international entrepreneurs leverage their international experience of living, studying, or working in foreign countries to build formal and informal networks for the international expansion of their ventures.…”
Section: International Networkingmentioning
confidence: 99%
“…open innovation and social media usage). While recent research explores the impact of the broader concept of international entrepreneurial culture and innovation (Buccieri et al, 2020), or the impact of IEO in knowledge acquisition (Lin et al, 2020), our article focuses in the more specific IEO construct, links in a novel way the different streams of international entrepreneurship, social media and innovation literature, and thus sheds new light on the reasons why some firms are more innovative than others (Hult et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Attaining useful resources is necessary for venture growth that can be achieved through managers' EO capabilities and competencies (Cassia & Minola, 2012). EO is essential for obtaining valuable resources such as knowledge, information, and opportunities, especially in the entrepreneurial process (Khodaei, Scholten, Wubben, & Omta, 2021; Lin, Cao, & Cottam, 2020; Yin, Hughes, & Hu, 2020). Coherently with RBV theory, it is advocated that firms' superior growth can be explained in terms of the availability of useful resources.…”
Section: Literature Reviewmentioning
confidence: 99%